Partially Purified Exo‐Polysaccharide from Lactobacillus Sakei Probio 65 with Antioxidant, α‐Glucosidase and Tyrosinase Inhibitory Potential. Issue 3 (June 2016) - Bajpai, Vivek K.; Rather, Irfan Ahmad; Park, Yong‐Ha
Abstract: In this study, partially purified exopolysaccharide (EPS) was isolated from the culture of Lactobacillus sakei Probio 65 by ethanol precipitation method with a yield of 220 mg/L. Analytical studies by Bradford and Phenol‐sulfuric methods revealed the presence of 1.6 and 78% total protein and total sugar contents in partially purified EPS, respectively. Further, to confirm the therapeutic potential, the EPS was evaluated for its inhibitory effects on α‐glucosidase and tyrosinase enzymes as well as its antioxidant potential in vitro . The partially purified EPS (10–200 mg/mL) showed potent efficacy on inhibiting α‐glucosidase and tyrosinase enzymes by 7.05–60.18% and 13.17–62.85%, respectively. In antioxidant assays, the EPS displayed considerable amount of antioxidant efficacy on scavenging 1, 1‐diphenyl‐2‐picryl hydrazyl and nitrite radicals, as well as its superoxide dismutase‐like activity by 49.56, 58.12 and 61.41%, respectively. Moreover, EPS showed potent reducing power capacity along with total phenolic content 20.38 µg/mg of gallic acid equivalent (GAE). Practical Applications: Free radicals play a very important role in food deterioration and disease progression. Hyperglycemia is believed to increase the production of free radicals and reactive oxygen species, leading to oxidative tissue damage and diabetic complications. Tyrosinase, a copper‐containing polyphenol oxidase, plays a highly critical role in forming melanin pigments. Lactic acid bacteria (LAB) have wide applications in food, cosmetic and medicine industries due to being Generally Recognized As Safe (GRAS) and multitude of therapeutic and functional properties. In this study, partially purified exopolysaccharide (EPS) was isolated from the culture of Lactobacillus sakei Probio 65 which exhibited potent antioxidant, as well as α‐glucosidase and tyrosinase inhibitory effects. These findings confirm that LAB‐derived EPS has potential to be developed into dietary supplements, cosmetic, medicine and nutraceuticals.